Tuning the CO2 Hydrogenation Selectivity of Rhodium Single‐Atom Catalysts on Zirconium Dioxide with Alkali Ions - Li, Shang; Xu, Yuxing; Wang, Hengwei; Teng, Botao; Liu, Qin; Li, Qiuhua; Xu, Lulu; Liu, Xinyu; Lu, Junling (Angewandte Chemie International Edition, 2023)
Tuning the coordination environments of metal single atoms (M1) in single‐atom catalysts has shown large impacts on catalytic activity and stability but often barely on selectivity in thermocatalysis. Here, we report that simultaneously regulating both Rh1 atoms and ZrO2 support with alkali ions (e.g., Na) enables efficient switching of the reaction products from nearly 100 % CH4 to above 99 % CO in CO2 hydrogenation in a wide temperature range (240–440 °C) along with a record high activity of 9.4 molCO gRh−1 h−1 at 300 °C and long‐term stability. In situ spectroscopic characterization and theoretical calculations unveil that alkali ions on ZrO2 change the surface intermediate from formate to carboxy species during CO2 activation, thus leading to exclusive CO formation. Meanwhile, alkali ions also reinforce the electronic Rh1‐support interactions, endowing the Rh1 atoms more electron deficient, which improves the stability against sintering and inhibits deep hydrogenation of CO to CH4. Doping alkali ions (e.g., Na) into Rh1/ZrO2 enables complete switching of the reaction product from CH4 to CO in CO2 hydrogenation over a broad temperature range. It was found that Na+ ions change the surface intermediate from HCOO* to COOH* and render the Rh1 atoms electron deficient with restrained H2 activation capability and weakened CO adsorption, thus cooperatively boosting CO formation.